Chronic Simultaneous Administration Of Acetaminophen And Ethanol Depletes Purkinje Cells In The (Vermis) Cerebellar Cortex Of Adult Wistar Rats (Rattus Norvegicus) - FAKUNLE P.B; AJIBADE A.J; OYEWO E.B (International Journal of Pharma and Bio Sciences, 2011)
Acetaminophen, also known as paracetamol, is a drug with potent antipyretic and analgesic actions but with very weak anti-inflammatory activity while ethanol is a depressant and regarded as a social drug. However very scanty literature is available especially when these drugs are consumed chronically and simultaneously despite their high degrees of abuse and misuse on the purkinje cells in the vermis of the cerebellum. In this study Forty adult wistar rats of average weight 150±20.2g were randomly distributed into four groups of treatments T1,T2T3 and control C (N=10) . The animals were fed on standard laboratory mouse chow with water provided ad libitum. For a period of six weeks, animals in group T1 received 100mg/Kg.bwt. acetaminophen and 25% ethanol in 2% sucrose solution while group T2 animals received 25% ethanol in 2% sucrose solution. T3 animals were given 100mg/Kg.bwt. acetaminophen and group C animals were given only distilled water. The animals were sacrificed by cervical dislocation and the cerebellar cortex were dissected out and processed for routine histological techniques. Shrunken brains were seen in the treatment groups T1 and T2 with significant brain weight loss (P<0.01) compared to the control. Significantly reduced purkinje cells neuronal density (P<0.05) of 49% and 43% neuronal loss respectively in treatment groups T1 and T2 compared to control group was recorded. The purkinje cells reduction observed as well as brain weight loss may adversely affect the normal functions of the cerebellum being a comparator and coordinator.